DHCR7 rs12785878 T>C Polymorphism Is Associated With an Increased Risk of Early Onset of Alzheimer's Disease in Chinese Population - Liu, Xixi; Wu, Pengfei; Shen, Lu; Jiao, Bin; Liao, Xinxin; Wang, Haochen; Peng, Jiangnan; Lin, Zhangyuan (Frontiers in Genetics, 2021)
Background: Vitamin D insufficiency has been implicated as a risk factor for Alzheimer disease (AD) in several studies. Recently, four single nucleotide polymorphisms (SNPs) to be genome-wide significant for 25(OH)D were identified to have association with risk of AD. These include rs2282679 in GC, rs10741657 near CYP2R1, rs12785878 near DHCR7 and rs6013897 in CYP24A1. However, the association between these polymorphism and AD susceptibility in Chinese population remains unclear. Methods: A case–control cohort study was conducted in 676 AD patients and 551 normal controls in order to find out whether the four SNPs account for risks in Chinese AD. Genotyping was determined by PCR and SNaPshot sequencing. Statistical significance was set at 0.0125(0.05/4) based on Bonferroni correction. Findings: Rs12785878 was found to be significantly associated with increased risk of early-onset Alzheimer’s disease (EOAD) (p=0.002, OR=1.542). There was no statistical significance of other three SNPs between the two groups. Interpretation: Our results suggested that rs12785878 might be associated with increased risk of EOAD in Chinese population, while other polymorphisms related to Vitamin D insufficiency might not be. However, due to the limited data in this study, replication studies in a larger sample are required.